Pengalaman Belajar Sosial-Emosional dan Literasi Digital dalam Mengembangkan Resiliensi Siswa Sekolah Dasar - Wiwik Lestari (Jurnal Keluarga Sehat Sejahtera, 2026)
The development of digital technology has brought about significant changes to the lives of primary school pupils, both academically and in social-emotional terms. On the one hand, technology provides extensive access to learning; on the other, it presents challenges such as smartphone addiction, poor emotional control, and a decline in the quality of social interaction. These circumstances call for the strengthening of resilience as pupils’ ability to cope with various pressures and learning challenges in the digital age. This study aims to understand primary school pupils’ experiences in developing resilience through social-emotional learning and digital literacy. The study employed a descriptive phenomenological approach, involving 12 pupils in Years 5–6 and 3 teachers from two state primary schools in the city of Medan. Data were collected through in-depth interviews, observation, and documentation, and subsequently analysed through data reduction, thematic categorisation, and interpretation of the participants’ experiences. The research findings indicate that social-emotional learning helps students recognise and manage their emotions, enhances empathy, and develops their ability to adapt to various learning challenges. Digital literacy provides positive experiences in using technology critically, wisely, and responsibly. The integration of these two learning experiences fosters student resilience through improved self-control, problem-solving skills, and the ability to cope with academic and social pressures. This study proposes the Socio-Digital Resilience Model, which explains that students’ resilience develops through the interaction of social-emotional competencies and digital literacy as key resources for addressing learning challenges in the digital age.The development of digital technology has brought about significant changes to the lives of primary school pupils, both academically and in social-emotional terms. On the one hand, technology provides extensive access to learning; on the other, it presents challenges such as smartphone addiction, poor emotional control, and a decline in the quality of social interaction. These circumstances call for the strengthening of resilience as pupils’ ability to cope with various pressures and learning challenges in the digital age. This study aims to understand primary school pupils’ experiences in developing resilience through social-emotional learning and digital literacy. The study employed a descriptive phenomenological approach, involving 12 pupils in Years 5–6 and 3 teachers from two state primary schools in the city of Medan. Data were collected through in-depth interviews, observation, and documentation, and subsequently analysed through data reduction, thematic categorisation, and interpretation of the participants’ experiences. The research findings indicate that social-emotional learning helps students recognise and manage their emotions, enhances empathy, and develops their ability to adapt to various learning challenges. Digital literacy provides positive experiences in using technology critically, wisely, and responsibly. The integration of these two learning experiences fosters student resilience through improved self-control, problem-solving skills, and the ability to cope with academic and social pressures. This study proposes the Socio-Digital Resilience Model, which explains that students’ resilience develops through the interaction of social-emotional competencies and digital literacy as key resources for addressing learning challenges in the digital age.